Výroční vědecká konference CZECRIN 2022 Sborník abstraktů - Součková, Lenka (Masaryk University Press, 2022)
Title in English: CZECRIN Annual Symposium 2022: Abstract book Collected abstracts of lectures presented during the scientific conference of the national infrastructure CZECRIN which supports academic clinical trials in the Czech Republic.